Peristicta guarellae sp. nov. from Brazil (Odonata: Protoneuridae) - Anjos Dos Santos, Danielle (2013)
Peristicta guarellae sp. nov. (holotype: Brazil, Paraná State, Exc. 399/col. 3, stream in km 50 of Curitiba-Ponta Grossa route [BR 376], about 25◦2008 S, 49◦5115 W, 21 November 1971, N. D. Santos leg., deposited in the Collection of Museu Nacional, Universidade Federal do Rio de Janeiro?, Rio de Janeiro, Brazil) is described and illustrated.An identification key for males of Peristicta (excluding P. lizeria Navás), comparisons and comments on other species of the genus are presented.